Study of the bioaccumulation of tinzaparin in renally impaired patients when given at prophylactic doses - The STRIP study. Issue 174 (February 2019) - Projean, D.; Lalonde, S.; Morin, J.; Nogues, E.; Séguin, A.; Vincent, A.; Lafrance, J.P.; Masson, V.; Kassis, J.; Fafard, J.; Lordkipanidzé, M.
Highlights: Accumulation of LMWH is a concern in severe chronic kidney disease (CKD). 28 subjects with severe CKD received prophylactic tinzaparin for up to 8 days. All had undetectable trough anti-Xa levels; half had undetectable peak levels. Prophylactic tinzaparin dosing didn't incur clinically significant bioaccumulation.